PROGRAM BIMBINGAN DAN KONSELING KOMPREHENSIF UNTUK MENGEMBANGKAN STANDAR KOMPETENSI SISWA - Bhakti, Caraka Putra (STKIP Andi Matappa, 2017)
Comprehensive guidance and counseling programs are based on achievement of developmental tasks, potential development, and alleviation of counselee problems. Developmental tasks are formulated as competency standards to be achieved by counselors, so this approach is also called standard-based guidance and counseling. Standards of student competence refers to Standards Independence Competence Learners (SKKPD) which is divided into 11 aspects of development. Successful implementation of comprehensive guidance and counseling program is the fulfillment of six characteristics, namely holistic, systematic, balanced, proactive, integration in school curriculum, and reflection. Procedures in the preparation of comprehensive guidance and counseling programs are planning (planning), organizing (organizing), implementation (penging), and evaluation (evaluation). Implementation of guidance and counseling programs is supported by the availability of skilled human resources. Teacher guidance and counseling / counselors are expected a set of knowledge and skills that support the implementation of the program. A full knowledge of developmental theory. Counselor's skills are to coordinate with various parties in implementing guidance and counseling program. The counselor has a strong leadership in running the guidance program, and has a proportional time management skills that is 80% of the time counseling and guidance services are directive in the learners while 20% of the service time is for the activity of the program management and system support